Helicobacter Pylori and Autoimmune Diseases: Involving Multiple Systems - Wang, Li; Cao, Zheng-Min; Zhang, Li-Li; Dai, Xin-can; Liu, Zhen-ju; Zeng, Yi-xian; Li, Xin-Ye; Wu, Qing-Juan; Lv, Wen-liang (Frontiers in Immunology, 2022)
The modern Gastroenterology have witnessed an essential stride since Helicobacter pylori was first found in the stomach and then its pathogenic effect was discovered. According to the researches conducted during the nearly 40 years, it has been found that this bacterium is associated with a natural history of many upper gastrointestinal diseases. Epidemiological data show an increased incidence of autoimmune disorders with or after infection with specific microorganisms. The researches have revealed that H. pylori is a potential trigger of gastric autoimmunity, and it may be associated with other autoimmune diseases, both innate and acquired. This paper reviews the current support or opposition about H. pylori as the role of potential triggers of autoimmune diseases, including inflammatory bowel disease, autoimmune thyroiditis, type 1 diabetes mellitus, autoimmune liver diseases, rheumatoid arthritis, idiopathic thrombocytopenic purpura, systemic lupus erythematosus, as well as Sjogren's syndrome, chronic urticaria and psoriasis, and tried to explain the possible mechanisms.